Nomenclatural changes in Anastatus Motschulsky and the description of Anastatus eurycanthae Gibson n. sp. (Eupelmidae: Eupelminae), an egg parasitoid of Eurycantha calcarata Lucas (Phasmida: Phasmatidae) from Papua New Guinea - Gibson, Gary A. P.; Dewhurst, Charles; Makai, Simon (Zootaxa, 2012)
Anastatus eurycanthae Gibson n. sp. (Eupelmidae: Eupelminae) is newly described as an egg parasitoid of Eurycanthacalcarata Lucas (Phasmida: Phasmatidae), an important pest of oil palm in Papua New Guinea. Both sexes are describedand illustrated by macrophotography and scanning electron microscopy. Basic biological data are provided on the parasi-toid. Six species are transferred from A. (Anastatus) Motschulsky to other genera, namely Eupelmus tennysoni Girault(1921) revived comb., Eupelmus (Eupelmus) darwini (Girault 1915) n. comb., Reikosiella (Hirticauda) pasteuri (Girault1915) n. comb., R. (Hirticauda) tricolor (Girault 1915) n. comb., Tineobius (Tineobius) adamsi (Yoshimoto & Ishii 1965) n. comb., and T. (Tineobius) crassipes (Yoshimoto & Ishii 1965) n. comb.